Long COVID treated successfully with antivirals in a rituximab-treated follicular lymphoma patient with persistent negative-antibodies to SARS-CoV2 - Elias Tayar (16488567) (2023)
Long COVID is a well-known complication to COVID-19 that affect millions of people worldwide and causes wide range of symptoms. We present a rare case of a previously diagnosed follicular lymphoma patient, who had a long COVID with persistent negative SARS-CoV-2 antibodies and required an aggressive antiviral treatment. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1016/j.heliyon.2023.e17149